Isolasi dan Karakterisasi Bakteri Asam Laktat dari Fermentasi Kombucha Berbasis Teh, Mangga, dan Nanas: Isolasi dan Karakterisasi Bakteri Asam Laktat dari Fermentasi Kombucha Berbasis Teh, Mangga, dan Nanas - Raissa Putri Sugiyarto; Laela Nur Rokhmah; Farah Nabila Reza Putri; Nena Isnaini Chahya Negara (Journal Science Innovation and Technology (SINTECH), 2026)
Kombucha is a fermented beverage produced by the activity of symbiotic microorganisms in the form of lactic acid bacteria (LAB), acetic acid bacteria, and yeast that are combined in SCOBY. Variations in fermentation substrates, such as tea and fruit juice, are thought to affect the microbiological characteristics of the kombucha produced. This study aims to isolate lactic acid bacteria (LAB) from kombucha using MRSA media, characterize the morphology of the isolated bacterial colonies and cells, and determine the gram staining type of lactic acid bacteria (LAB) isolates from kombucha fermentation based on tea, mango juice, and pineapple juice at different fermentation times. The research method used was an experimental method with variations in substrate and fermentation time (day 7 and 14). LAB isolation was performed using MRS Agar medium through serial dilution to 10??, followed by macroscopic observation of colonies and gram staining for microscopic identification. The results showed that all BAL isolates from various treatments had gram-positive characteristics with rod-shaped cells. Macroscopically, the colonies showed variations in shape, color, elevation, and colony edges, which were influenced by the type of substrate, dilution level, and fermentation time. It can be concluded that differences in substrate and fermentation time did not affect the basic microscopic characteristics of BAL cells, but did influence the morphological variation of the colonies.